An analysis of the trickle-down effect of supervisor knowledge hiding on subordinate knowledge hiding based on displaced aggression theory - Tang, Yanzhao; Zhu, Hong-Ming; Du, Xingcheng (Frontiers in Psychology, 2022)
The harm of horizontal knowledge hiding behavior (colleague–colleague) to individuals and organizations has been discussed and confirmed by many studies. The negative consequences of top-down (supervisor–subordinate) knowledge hiding have now emerged as a new focus of research. This study aims to enrich the understanding of the consequences of supervisor knowledge hiding by exploring its trickle-down effect and mechanism. Based on the displaced aggression theory in psychology, this paper analyzes and examines the cognitive psychological process and mechanism informing employee knowledge hiding from colleagues when faced with their supervisor's malicious knowledge hiding behavior. Using a three-stage time-lag questionnaire survey strategy, we collect 233 valid samples of full-time employees from representative provinces and cities in China, covering multiple industries. The following findings are observed: (1) Supervisor knowledge hiding from subordinates (SKHS) positively affects subordinate knowledge hiding from colleagues (SKHC); (2) Revenge motivation plays a mediating role; (3) Traditionality weakens the influence of supervisor knowledge hiding on a subordinates’ revenge motivation. This study confirms the trickle-down effects of supervisor knowledge hiding behavior, extends research on the consequences of top-down knowledge hiding and its mechanism and provides new insights for organizational practice.